2017
DOI: 10.1155/2017/2618587
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Processing Abilities of Parkinson’s Disease Patients

Abstract: Since Parkinson's Disease (PD) primarily affects older people, a majority of PD patients have age-related hearing loss (HL) that will worsen over time. The goal of this study was to assess peripheral and central auditory functions in a population of PD patients and compare the results with a group of age-matched control subjects. Study participants included 35 adults with PD (mean age = 66.9 ± 11.2 years) and a group of 35 healthy control subjects (mean age = 65.4 ± 12.3 years). Assessments included questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 62 publications
2
51
3
3
Order By: Relevance
“…Thus, from these findings, individuals with PD would be expected to present higher frequency of complaints and auditory alterations as a consequence of dopaminergic deficit. However, previous clinical studies have revealed controversial findings regarding the perception of hearing difficulties and the audiometric profile in the disease (11,12) .…”
Section: Introductionmentioning
confidence: 97%
“…Thus, from these findings, individuals with PD would be expected to present higher frequency of complaints and auditory alterations as a consequence of dopaminergic deficit. However, previous clinical studies have revealed controversial findings regarding the perception of hearing difficulties and the audiometric profile in the disease (11,12) .…”
Section: Introductionmentioning
confidence: 97%
“…These speech deficits hinder their ability to verbally communicate and interfere with activities of daily living. Persons with PD may report difficulty being understood on the phone, at a drive-through restaurant, or at a social event where there is background noise [7][8][9]. Some people have essentially resigned themselves to the fact that their loved ones must speak for them or order for them.…”
Section: Introductionmentioning
confidence: 99%
“…Living with PD and its associated speech impairment, in particular, has psychosocial and emotional impact. Patients often report a tendency to withdraw from friends and family, feeling isolated and depressed [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, there is no direct evidence that the auditory deficits presented by PD patients are associated with dopaminergic neuron loss. However, there is evidence demonstrating that these auditory deficits are not merely age‐related hearing loss, but are rather components of dysfunctional cognitive and sensory processing (Folmer, Vachhani, Theodoroff, Ellinger, & Riggins, ; Lai, Liao, Lin, Lin, & Sung, ; Yylmaz et al, ). As such, PD‐related auditory deficits also involve attentional, motivational and motoric components likely associated to parallel cortico‐thalamic‐striatal‐cerebellar loops modulated by dopamine (Clark, Adams, Dykstra, Moodie, & Jog, ; Gräber, Hertrich, Daum, Spieker, & Ackermann, ; Schröder, Nikolova, & Dengler, ; Shalash et al, ; Vitale et al, ).…”
Section: Introductionmentioning
confidence: 99%